UJI KUALITAS BRIKET SABUT KELAPA SEBAGAI SUMBER ENERGI BIOAMASSA ALTERNATIF - E. Kambey; D. Tooy; D. Rumambi (COCOS, 2023)
ABSTRACT Indonesia has the potential of abundant natural resources in agriculture such as coconut plantations. The area of coconut plantations in Indonesia reaches 3,728,600 ha. Currently, Indonesian agricultural commodities are well known and their demand is increasing from various countries such as technological developments. Indonesia is able to produce 18.3 million tons of coconut in a year this number can increase from year to year so that Indonesia becomes the largest producer in this industry. In North Sulawesi, coconut yields in 2021 will reach 265,761 tons. North Sulawesi produces a lot of coconut, mostly in the form of copra. Coconut coir is used as a raw material for making charcoal briquettes that are environmentally friendly, easy to obtain and have high economic value. Based on the above, it is felt necessary to conduct research on coco briquettes by looking at the effect of mixing adhesives on the quality of briquettes. So the purpose of testing the water content, calorific value, rate of combustion and flame test of coconut fiber briquettes and starch as adhesives. The lowest air content is in the percentage of 95%: 5%, which is 18.97%, while the highest air content is in the mixing proportion of 90%: 10%, which is 19.56%. The results of the average briquette test showed that the lowest calorific value was 2244,614 cal/g using 5% adhesive, while the highest calorific value was 3225,8648% using 7.5% adhesive. The fastest average burning rate was in the 5% treatment with a time of 0.00126140 (g/s) and the longest burning rate was in the 7.5% treatment with a time of 0.001702662 (g/s). The fastest Self Burning Time is at a mixing proportion of 90%:10% with an initial ignition time of 05 minutes 10 seconds, while the longest Self Burning Time is at a percentage of 95%:5% with an initial ignition time of 06 minutes 08 seconds. The results of the test for boiling 1 liter of water, the sample mixture of 95% coconut coir briquettes: 5% starch takes a long time to boil 1 liter of water, which is 27 minutes 45 seconds. For 90% coconut coir briquette mixture: 10% starch, it takes a little faster, namely 25 minutes 33 seconds. Keywords: Charcoal briquettes, Coco coir, Initial ignition time, Biomass energy